A Bibliometric and Thematic Analysis of Digital Marketing Research in Reputable Journals (2010-2024) - Judijanto, Loso; Rauf, Nuzmerini; Anani, Siske; Idrus, Rini Angriani (West Science Business and Management, 2025)
This study presents a bibliometric and thematic analysis of digital marketing research published in reputable journals between 2010 and 2024, utilizing VOSviewer to map structural, conceptual, and temporal developments in the field. A total of curated Scopus-indexed journal articles were analyzed to identify key trends, prolific authors, collaborative networks, and evolving research themes. The results reveal that digital marketing has undergone significant transformation, with a shift from early emphases on technological enablers such as big data and artificial intelligence to more recent interests in consumer behavior, social media engagement, and sustainability. Co-authorship analysis highlights dominant scholarly clusters in both Western and emerging economies, reflecting a globally distributed knowledge base. Country-level collaboration networks further underscore the increasing contribution of nations like India, Indonesia, and Spain to the digital marketing discourse. Thematic clustering and temporal mapping indicate a maturation of the field, with growing interdisciplinary integration and practical relevance. This study provides critical insights for academics, practitioners, and policymakers aiming to navigate and contribute to the evolving landscape of digital marketing research.